Investigation of Energy Commercial Metering set’s Elements Errors - Deksnys, R. P.; Staniulis, R. (Elektronika ir Elektrotechnika, 2010)
Metering of electric power and energy in electricity market requires paying more attention to accuracy of metering systems and scientific reasoning of metering formal documents. Electric energy metering of proper accuracy is fairly complicated problem, which requires systematic attitude into various influencing factors and also compatibility of technical and organizational tasks. Errors of electric energy metering circuits are investigated and their dependence on power network operational regimes, current and voltage transformers measured values and character, value of secondary circuits load are determined in this paper. Accuracy of energy metering is investigated and methodology of increase of commercial metering circuits’ accuracy is proposed.